Power loss estimation of polymeric housing surge arrester using leakage current and temperature approach. (August 2019) - Novizon; Malek, Z A; Ahmad, M H; Waldi, E P; Aulia; Laksono, H D; Riska, N
Abstract: The good operation of metal oxide surge arresters depends on the increment of temperature. If the arresters cannot quickly disperse the absorbed energy into the ambient, arresters temperature may exceed its operating temperature limit. Consequently, thermal runaway occurs and results in power loss. In this paper, thermal characteristics and thermal stability based on power loss calculation were investigated. Applied voltages, leakage current, and temperature were the main parameters consideration. The power loss calculated by the electrical model is the input to the thermal model. The electro-thermal model is used to determine the two intersection points (stable operating point and the thermal instability point) of the power input and heat loss curves. The results show that irrespective of the different magnitude voltages applied to the arrester and different energy ratings for the elements, the power loss occurs at the certain applied voltage.